Monogastric animal feed. - Loh, Teck Chwen; Foo, Hooi Ling (2009)

(untitled)
The present invention relates an improved feed additive or food supplement formulation obtained from more than one strain of lactic acid bacteria. The feed additive or supplement is used to feed monogastric animals such as avian, fowl. Moreover, the feed provides better growth and feed utilization for monogastric animals. Further, the animal feed can be used for controlling food intake in the animals.